Eagle's syndrome with a cyst around pseudoarticulation surgically treated using a transoral approach: Case report - Do Yoon Jeong; Jiwoong Cho; Jeonghyun Oh (Elsevier, 2021)
Eagle's syndrome is a disease that can cause a variety of clinical symptoms, including pain in the head, neck, and face. The criteria for classifying the elongated styloid process and stylohyoid complex syndrome caused by ossification of the stylohyoid ligament were introduced. A 55-year-old male patient, without a history of trauma, visited the outpatient department with a history of intermittent ear pain and ear fullness while eating for the past 2 weeks. Computed tomography of the neck revealed that the right styloid process was pseudoarticulated with the hyoid bone, and round cystic changes were observed in the periphery. We performed operation using the transoral approach and the patient showed improvement in symptoms.